(untitled) (Port Harcourt Medical Journal, 2025)
Background: Enterocutaneous fistulae are associated with significant morbidity, mortality and daunting management challenges. This study aims to evaluate the presentation and management outcomes of patients with enterocutaneous fistula in a Sub-Saharan setting. Methods: A retrospective study of patients with enterocutaneous fistula in Ahmadu Bello University Teaching Hospital, Zaria, Kaduna State, Nigeria from January, 2015 to December, 2019. The notes, charts, management and outcome of these were reviewed. Data was analyzed with the IBM Statistical Product and Service Solutions (SPSS) version 25.0 and p values ≤ 0.05 regarded as statistically significant. Results: Data from 56 patients (26 males and 30 females, male:female ratio of 1:1.2) were analyzed. Most (91.07%) of the fistulae were post-operative and more in those aged 21-30 years (42.86%). Majority (87.50%) had high output fistulae and 82.14% had deranged electrolytes at presentation. Non-operative management was done for 44.64% of the patients, the rest (55.36%) had surgery. Survival was the outcome in 87.50%, mortality was recorded in 12.50%, with sepsis accounting for a greater percentage (7.14%) of the mortalities. Fistula aetiology, operation before admission, co-morbidities, electrolyte derangements, hypoalbuminaemia, anaemia, and fistula effluent volume were significantly related to mortality (p values of 0.003, 0.001, 0.015, 0.001, 0.004, 0.003 and 0.017 respectively). Conclusion: Most fistulae seen were post-operative. Non-operative treatment led to healing in 44.64% of all cases with mortality of 12.50%. Fistula aetiology, operative intervention before admission, co-morbidities, electrolyte derangements, hypoalbuminaemia, anaemia, and volume of fistula effluent were significantly related to mortality.